The effect of age on the systemic inflammatory response in patients with community‐acquired pneumonia. (18th July 2014) - van Vught, L. A.; Endeman, H.; Meijvis, S. C.; Zwinderman, A. H.; Scicluna, B. P.; Biesma, D. H.; van der Poll, T.; Paul, M.
Abstract Community‐acquired pneumonia (CAP) is a major cause of morbidity and mortality worldwide. Increasing age has been associated with elevated circulating levels of pro‐inflammatory mediators. We aimed to determine the impact of ageing on the systemic inflammatory response to CAP. In total 201 CAP patients were enrolled. Blood samples were obtained upon presentation, and on days 2, 3 and 5. For the current analysis patients ≤50 and ≥80 years were included. The Pneumonia Severity Index (PSI) score was calculated at presentation. The study encompassed 46 CAP patients aged ≤50 years (median 37 years) and 41 CAP patients aged ≥80 years (median 84 years). In both groups Streptococcus pneumoniae was the common causative microorganism. Whereas most young patients had a PSI score of I (54%), 98% of elderly patients had a PSI score ≥III (p <0.001). Four elderly patients died vs. none of the young patients (p 0.045). Older patients demonstrated lower serum C‐reactive protein levels on admission and during the course of their hospitalization (p 0.001) in spite of more severe disease. Serum concentrations of pro‐inflammatory (interleukin (IL)‐6 and IL‐8) and anti‐inflammatory cytokines (IL‐10 and IL‐1 receptor antagonist) did not differ between age groups, although admission IL‐8 levels tended to be higher in elderly patients (p 0.05). Cytokine levels were positively correlated with PSI in young but not in elderly patients. These results suggest that elderly patients show an absolute (C‐reactive protein) or relative (cytokines) reduction in their systemic inflammatory response on admission for CAP.